2020
DOI: 10.1002/smi.2924
|View full text |Cite
|
Sign up to set email alerts
|

Devoted fans release more cortisol when watching live soccer matches

Abstract: Why do some sports fans experience intense emotions when watching live matches? Identity fusion is a strong form of group alignment in which personal and group identities are activated synergistically to produce a visceral sense of 'oneness' with one's team. Here we examine the role of fusion (using a three‐item state measure with high internal validity) in elevating salivary cortisol levels while watching football (n = 41). Our evidence was gathered at field laboratories during the 2014 sFIFA World Cup in Nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Some aspects of the process by which shared dysphoric experiences lead to fusion have now been measured physiologically, as well as by using psychometric tests and self-report. For example, a recent longitudinal study of Brazilian fans during the 2014 FIFA World Cup revealed that increased heart rate and cortisol levels during live matches predicted higher levels of fusion over time (Newson et al, under review). Efforts have also been made to explore the physiological processes by which out-group threat motivates self-sacrifice in highly fused individuals.…”
Section: Shared Essence Fusion and Willingness To Fight And Die Formentioning
confidence: 99%
“…Some aspects of the process by which shared dysphoric experiences lead to fusion have now been measured physiologically, as well as by using psychometric tests and self-report. For example, a recent longitudinal study of Brazilian fans during the 2014 FIFA World Cup revealed that increased heart rate and cortisol levels during live matches predicted higher levels of fusion over time (Newson et al, under review). Efforts have also been made to explore the physiological processes by which out-group threat motivates self-sacrifice in highly fused individuals.…”
Section: Shared Essence Fusion and Willingness To Fight And Die Formentioning
confidence: 99%
“…Moreover, while there is evidence suggesting that shared arousal is a complex bio-social phenomenon 9 , integrated research examining physiological and social effects in tandem is rare. Studies have found that arousing social gatherings can lead to the synchronization of autonomic activity among participants, including spectators 10 , 11 , and that shared arousal is associated with intense pro-group sentiments 1 , 12 14 . However, as the literature concerning physiological synchrony is still under development, there is little theoretical precision or methodological consolidation 15 , and as a result the links between these analytic levels are not yet fully understood 16 .…”
Section: Introductionmentioning
confidence: 99%
“…The noted anthropologist Edmund Leach, for example, describes the process of gardening among the Kachin of highland Burma as continually oscillating between practical instrumental elements necessary to ensure plant growth and "aesthetic frills" that are technically unnecessary but conventional aspects of horticulture, identifying the gardener as a bona fide member of the Kachin cultural group (Leach, 1954). Much the same may be said of spectator sports such as football (Newson et al, 2020), which have many very ritualistic aspects (from "Mexican waves" to the wearing of special scarves) but also very causally transparent procedures for achieving end goals (such as the placement of a ball at the back of a net). We return briefly to this point in section 2.4.1. when discussing the affiliative aspects of ritual participation and also in connection with quasi-instrumental rituals.…”
Section: Stance Selectionmentioning
confidence: 99%